FDI in the Era of Globalization: Some Issues - Singh, Anchal (Indian Journal of Finance, 2010)
With the onset of 1990s, the Indian government realized that the foreign direct investment can spur the economic growth and hence initiated a slew of economic reforms. Moreover, in 2003, the second generation reforms were started to integrate the country's economy with the world economy, through increasing the flow of FDI in the world. FDI plays a pivotal role in the economic development of the host country and provides a launching pad from where they can they can make further improvements. Any form of investment that earns interest in enterprises and functions outside the domestic territory of investor can be treated as FDI. For an investment to be classified as an FDI, the parent firm needs to have at least 10% of the ordinary shares of its foreign affiliates.